Intraluminal bubble dynamics induced by lithotripsy shock wave. (8th November 2016) - Song, Jie; Bai, Jiaming; Zhou, Yufeng
Abstract: Extracorporeal shock wave lithotripsy (ESWL) has been the first option in the treatment of calculi in the upper urinary tract since its introduction. ESWL-induced renal injury is also found after treatment and is assumed to associate with intraluminal bubble dynamics. To further understand the interaction of bubble expansion and collapse with the vessel wall, the finite element method (FEM) was used to simulate intraluminal bubble dynamics and calculate the distribution of stress in the vessel wall and surrounding soft tissue during cavitation. The effects of peak pressure, vessel size, and stiffness of soft tissue were investigated. Significant dilation on the vessel wall occurs after contacting with rapid and large bubble expansion, and then vessel deformation propagates in the axial direction. During bubble collapse, large shear stress is found to be applied to the vessel wall at a clinical lithotripter setting (i.e. 40 MPa peak pressure), which may be the mechanism of ESWL-induced vessel rupture. The decrease of vessel size and viscosity of soft tissue would enhance vessel deformation and, consequently, increase the generated shear stress and normal stresses. Meanwhile, a significantly asymmetric bubble boundary is also found due to faster axial bubble expansion and shrinkage than in radial direction, and deformation of the vessel wall may result in the formation of microjets in the axial direction. Therefore, this numerical work would illustrate the mechanism of ESWL-induced tissue injury in order to develop appropriate counteractive strategies for reduced adverse effects.